Plasma alkylresorcinols, biomarkers of whole-grain intake, are not associated with progression of coronary artery atherosclerosis in postmenopausal women with coronary artery disease. Issue 2 (23rd April 2015) - McKeown, Nicola M; Hruby, Adela; Landberg, Rikard; Herrington, David M; Lichtenstein, Alice H
Abstract: Objective: The objective of the present study was to examine the relationship between plasma alkyresorcinol (AR) concentrations, which are biomarkers of whole-grain intake, and atherosclerotic progression over 3 years in postmenopausal women with coronary artery disease. Design: Plasma AR concentrations were measured by a validated GC–MS method in fasting plasma samples. Atherosclerosis progression was assessed using change in mean minimal coronary artery diameter (MCAD) and percentage diameter stenosis (%ST), based on mean proximal vessel diameter across up to ten coronary segments. Dietary intake was estimated using a 126-item interviewer-administered FFQ. Setting: A prospective study of postmenopausal women participating in the Estrogen Replacement and Atherosclerosis trial. Subjects: For the analysis of plasma AR concentrations and atherosclerotic progression, plasma samples and follow-up data on angiography were available for 182 women. Results: Mean whole-grain intake was 9·6 (se 0·6) servings per week. After multivariate adjustment, no significant associations were observed between plasma AR concentrations and change in mean MCAD or progression of %ST. Plasma AR concentrations were significantly correlated with dietary whole grains ( r =0·35, P <0·001), cereal fibre ( r =0·33, P <0·001), bran ( r =0·15, P =0·05), total fibre ( r =0·22, P =0·003) and legume fibre ( r =0·15, P =0·04), but not refined grains, fruit fibre or vegetable fibre. Conclusions: Plasma AR concentrations were not significantly associated with coronary artery progression over a 3-year period in postmenopausal women with coronary artery disease. A moderate association was observed between plasma AR concentrations and dietary whole grains and cereal fibre, suggesting it may be a useful biomarker in observational studies.